Overcoming Poverty and Inequality in South Africa : An Assessment of Drivers, Constraints and Opportunities - World Bank Group (World Bank, Washington, DC, 2018)
This report documents the progress South Africa has made in reducing poverty and inequality since the end of apartheid in 1994, with a focus on the period between 2006 and 2015. The main conclusions are as follows: First, by any measure, South Africa is one of the most unequal countries in the world. Inequality is high, persistent, and has increased since 1994. Second, although South Africa has made progress in reducing poverty since 1994, the trajectory of poverty reduction was reversed between 2011 and 2015, threatening to erode some of the gains made since 1994. High levels of inequality and low intergenerational mobility act as a brake on poverty reduction and as a result poverty is high for an upper middle-income country. Poverty is consistently highest among black South Africans, the less educated, the unemployed, female-headed households, large families, and children. Further, poverty has a strong spatial dimension in South Africa, a demonstration of the enduring legacy of apartheid. Poverty remains concentrated in previously disadvantaged areas, such as the former homelands – areas that were set aside for black South Africans along ethnic lines during apartheid. Third, high levels of income polarization are manifested in very high levels of chronic poverty, a few high-income earners and a relatively small middle class. Fourth, the role of skills and labor market factors have grown in importance in explaining poverty and inequality while the role of gender and race, though still important, has declined, presenting an opportunity for policy to influence poverty and inequality outcomes. Social protection remains important in reducing extreme poverty, but the fiscal space for further expansion is limited. Low growth perspectives in the coming years suggest poor prospects of eliminating poverty by 2030 as envisaged in the National Development Plan. Looking ahead, accelerating poverty and inequality reduction will require a combination of policies that seek to unlock the full potential of labor markets and promote inclusive growth through skilled job creation.